The Impact of Artificial and Natural Additives in Meat Products on Neurocognitive Food Perception: A Narrative Review - Marius-Mihai Ciobanu; Elena-Iuliana Flocea; Paul-Corneliu Boișteanu (Foods)
The holistic sensory experience creates a unified perception that influences consumer memory. Consumer interest in clean label products underlines an accelerated trend towards products without artificial additives. From a sensory point of view, food appeal is significantly influenced by how additives actively participate in the organoleptic properties of the final product. This research aims to shed light on the impact of artificial and natural additives in meat products on neurocognitive food perception, which is essential for understanding how they influence the consumer’s final decision and direct food trends. Different neural mechanisms involved in multimodal sensory integration confirm differences in perception of meat products containing artificial and natural additives. Analysis confirms that neurocognitive perception integrates organoleptic sensations to form a complete sensory experience. The encephalon simultaneously processes multimodally integrated stimuli from organoleptic properties, reaching the orbitofrontal cortex and other regions involved in the neuroprocessing of the final product. The reformulation and development of meat products need a detailed analysis of the impact of additives on sensory properties contributing to the shaping of consumption trends.